45-degree rafting in Ni-based superalloys: A combined phase-field and strain gradient crystal plasticity study. (May 2020) - Ali, Muhammad Adil; Amin, Waseem; Shchyglo, Oleg; Steinbach, Ingo
Abstract: 45 ° rafting of Ni-based superalloys has been investigated with the help of creep test simulations applying a strain gradient crystal plasticity model coupled to the multi-phase field method. This mode of rafting lies in between P- and N-type rafting modes. The model parameters are calibrated against experimental data for N-type rafting under high temperature and low stress creep condition. By increasing the stress level, the mixed-mode rafting of precipitates with a clear tendency toward formation of 45 ° rafts is observed. We show that the key factor for the occurrence of this type of rafting is the generation of highly localized creep strain of more than 10% due to non-homogeneous creep deformation in the form of slip bands. We have successfully captured the evolution of microstructure under high stress leading to production of localized shear bands. Graphical abstract: Highlights: Strain gradient crystal plasticity model is coupled with the phase-field framework. 3D creep simulations are performed in the high temperature, low stress regime. High stresses (>600 MPa) lead to so-called mixed mode rafting. Localized creep strain (¿10%) favors 45 ° rafting.